(untitled) (International Journal of Physiology, 2019)
Background The rubber industries use a greater variety of chemicals than any other branch of industry. The processing area is the site at which workers are exposed to many atmospheric contaminants. The impact of health hazards of latex in this group of workers is highly under reported and it is in this regards that an attempt in this study was made to assess the influence of latex and other chemicals on pulmonary function of workers engaged in rubber processing. Objective To assess the pulmonary function of workers engaged in processing of natural rubber Method This is a descriptive cross-sectional study involving 50 rubber workers who were selected from camps conducted in different parts of Kottayam district, Kerala. A portable vitalograph was used to assess the pulmonary functions-FEV1(Forced expiratory volume in 1st second), FEV1/FVC and FEF25–75%(Forced expiratory flow rate). Statistical analysis was done using excel and epi-info Results A statistically significant reduction was seen in the FEV1/FVC values among 80% of the rubber workers indicating obstructive airway disease. A statistically significant reduction was seen in the FEF 25–75% values among 26% of the rubber workers. Conclusion Rubber workers have a risk of developing obstructive and small airway diseases due to continuous exposure to latex and chemicals which are airway irritants. Health awareness and health promotion activities should be initiated among the workers to prevent and reduce the progress of pulmonary diseases.